Initial observation of CIN2 does not appear to reduce quality of life in women under 25 years of age. (16th May 2017) - Taghavi, Katayoun; Morell, Sára; Lamb, Jillian; MacNab, Helene; Innes, Carrie; Coffey, Kate; Williman, Jonathan; Simcock, Bryony; Sykes, Peter
Abstract : Background: Although the patient perspective is implicit in the practice of medicine, research evaluating this remains scarce. In a climate where clinicians and policy‐makers constantly strive to achieve more patient‐centred models of care, this omission warrants attention. Aim: To assess health‐related quality of life (HrQoL) in women under 25 years of age with cervical intra‐epithelial neoplasia grade 2 (CIN2) receiving conservative management (colposcopy follow‐up, with treatment if necessary) compared with those receiving immediate excisional treatment with large loop excision of the transformation zone (LLETZ). Methods: An observational study evaluating HrQoL was conducted at Christchurch Women's Hospital, New Zealand. Women undergoing conservative management for CIN2 were compared with those undergoing immediate excisional treatment in an age‐matched sample. The Short Form Health Survey 12 version 2 (SF‐12v2) was used to evaluate HrQoL. Secondary outcomes of anxiety and sexual function were also assessed. Results: One hundred and four women with CIN2 participated in the study. Of these, 63 (60%) received conservative management and 41 (40%) received immediate excisional treatment with LLETZ. We found no significant difference in HrQoL between the groups in a multivariate regression analysis adjusted for parity, smoking and socioeconomic status. There were also no significant differences in sexual function or anxiety. Conclusion: We found no difference in HrQoL by management strategy. Conservative management of CIN2 in women under 25 is unlikely to have an adverse impact on self‐reported HrQoL, anxiety or sexual functioning compared with conventional management.